School- and Community-Based Youth Suicide Prevention Interventions: Hot Idea, Hot Air, or Sham? - Kutcher, Stan (Can J Psychiatry, 2016)
Suicide in young people is a significant health concern, with numerous community- and school-based interventions promising to prevent suicide currently being applied across Canada. Before widespread application of any one of these, it is essential to determine its effectiveness and safety. We systematically reviewed the global literature on one of the most common community suicide prevention interventions in Canada and summarized data on 2 commonly applied school-based suicide prevention programmes. None of these has demonstrated effectiveness in preventing youth suicide or safety in application. Concurrently with their widespread distribution in Canada, the suicide rate in young women has increased—the first time in over 3 decades. Policy and regulatory implications of these findings are discussed.